Pathogenesis and management of fracture-related infection. (May 2020) - Depypere, M.; Morgenstern, M.; Kuehl, R.; Senneville, E.; Moriarty, T.F.; Obremskey, W.T.; Zimmerli, W.; Trampuz, A.; Lagrou, K.; Metsemakers, W-J.
Abstract: Background: Both fracture-related infections (FRIs) and periprosthetic joint infections (PJIs) include orthopaedic implant-associated infections. However, key aspects of management differ due to the bone and soft tissue damage in FRIs and the option of removing the implant after fracture healing. In contrast to PJIs, research and guidelines for diagnosis and treatment in FRIs are scarce. Objectives: This narrative review aims to update clinical microbiologists, infectious disease specialists and surgeons on the management of FRIs. Sources: A computerized search of PubMed was performed to identify relevant studies. Search terms included 'Fracture' and 'Infection'. The reference lists of all retrieved articles were checked for additional relevant references. In addition, when scientific evidence was lacking, recommendations are based on expert opinion. Content: Pathogenesis, prevention, diagnosis and treatment of FRIs are presented. Whenever available, specific data of patients with FRI are discussed. Implications: Management of patients with FRI should take into account FRI-specific features. Treatment pathways should implement a multidisciplinary approach to achieve a good outcome. Recently, international consensus guidelines were developed to improve the quality of care for patients suffering from this severe complication, which are highlighted in this review.